Nonaqueous arylated quinone catholytes for lithium–organic flow batteries. Issue 30 (16th July 2018) - Shin, Dong-Seon; Park, Minjoon; Ryu, Jaechan; Hwang, Inchan; Seo, Jeong Kon; Seo, Kwanyong; Cho, Jaephil; Hong, Sung You
Abstract : Chemically tailored quinone catholytes have been utilized for tubular lithium–organic flow batteries in a continuous electrolyte flow mode. Abstract : Chemically modified organic redox couples have the advantages of tunable redox properties, high solubility, environmental benignity, and cost effectiveness. Inspired by nature, a series of quinone derivatives bearing electron-donating methoxy or electron-withdrawing trifluoromethyl groups are synthesized in moderate to high yields by Pd-catalyzed Suzuki cross-coupling reactions. This study utilizes the synthetic quinones as redox-active organic molecules for nonaqueous lithium–organic flow batteries. The aryl moiety incorporated quinone scaffolds show enhanced electrochemical stability and rate capability. The nonaqueous catholyte, 2-phenyl-1, 4-naphthoquinone, reaches a cell voltage of ∼2.6 V and a specific capacity of 196 mA h g −1, while the discharge capacity is retained at ∼92% for 150 cycles. Moreover, the tubular lithium–organic flow battery system features stable cycle performance under a continuous circulation without clogging-associated intermittency flow.